PELATIHAN PEMASARAN USAHA RINTISAN ANEKA SNACK GLORIA DI BATURAJA GUNA MENINGKATKAN EKONOMI MASYARAKAT DIKELURAHAN SUKAJADI BATURAJA - Apriyani, Rini; Malini, Hema (INCIDENTAL : Journal Of Community Service and Empowerment, 2022)
This community service activity aims to provide marketing training for the pilot business of various Gloria snacks in Baturaja to improve the community's economy in the Sukajadi Baturaja Village which will be held on October 22, 2022. The training process is carried out using a learning method approach, namely demonstrations, lectures and questions and answers. This activity involved lecturers and students of STIE Dwi Sakti Baturaja in collaboration with 28 mothers who attended this activity. Based on the results of the evaluation of these activities, the enthusiasm of the participants during the training was quite high. This can be seen from the seriousness of the participants in participating in the training and inviting the implementation team to join again in providing training again with a different theme. With this training, it is hoped that participants will be able to market Gloria's various snack products not only in the Sukajadi Baturaja Village but outside the Sukajadi Baturaja Village.